2015
DOI: 10.14419/ijbas.v4i2.4421
|View full text |Cite
|
Sign up to set email alerts
|

Double right renal vein: clinical and surgical implications and review of the literature

Abstract: Context: Variations in renal vascular morphology are relatively common and involve both the renal arteries and the renal veins. Presence of supernumerary vessels is the variation most frequently encountered. Knowledge of such findings is valuable for urologists with regard to kidney transplantation, nephrectomy, vascular anastomosis, selective catheterization and many other surgical procedures on the kidneys. Objective: To report on a case of duplication of the right renal vein and its clinical and surgical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Anatomical variations of renal arteries and veins are often reported in several studies [5,6,9,10], as well as case reports of duplicity and triplicity [12][13][14][15][16]. In the present study there were found triple renal arteries on the left kidney and double renal veins on the right kidney.…”
Section: Discussionsupporting
confidence: 71%
“…Anatomical variations of renal arteries and veins are often reported in several studies [5,6,9,10], as well as case reports of duplicity and triplicity [12][13][14][15][16]. In the present study there were found triple renal arteries on the left kidney and double renal veins on the right kidney.…”
Section: Discussionsupporting
confidence: 71%
“…variation of renal arteries is extremely important for the vascular clinic and imageologists [3]. The accessory renal arteries range from 18.3% and 36.1% of the cases, on the right side the variation is from 11 to 16% and on the left side from 10 to 23%, and in both sides it can get to 5% [1,4,5,8]. In our study, two double bilateral renal arteries were found.…”
Section: Case Reportmentioning
confidence: 45%
“…Among all its anatomical variations one of the most common is the presence of additional renal arteries [4,5]. This occurrence can become a complicating factor in renal surgeries, and particularly in kidney transplants [4].…”
Section: Introductionmentioning
confidence: 99%